Fertility preserving options in patients with gynecologic malignancies - Eskander, Ramez N. (Am J Obstet Gynecol, 2011)
A proportion of reproductive age women are affected by gynecologic malignancies. This patient population is faced with difficult decisions, related to their cancer care and treatment, as well as future childbearing potential. Therefore, it is important for gynecologists to be familiar with fertility sparing management options in patients with cervical, ovarian, and endometrial cancer. In addition to understanding the surgical approaches available, providers should be able to counsel patients regarding their eligibility for and the indications and limitations of fertility sparing therapy for gynecologic cancer, allowing for appropriate referrals. A comprehensive PUBMED literature search was conducted using the key words “fertility preservation,” “cervical cancer,” “endometrial cancer,” “ovarian cancer,” “borderline tumor of the ovary,” “germ cell tumor,” “obstetrical outcomes,” “chemotherapy,” and “radiation.” The following review summarizes fertility sparing options for patients with cervical, ovarian and endometrial cancer, with an emphasis on appropriate patient selection, oncologic, and obstetric outcomes.